Suicidal ideation, attempt and associated factors among people with cancer attending cancer center, eastern Ethiopia - Nigussie, Kabtamu; Tesfaye, Dejene; Abdisa, Lemesa; Tolosa, Lidiya; Bete, Tilahun; Gemechu, Kabtamu; Negash, Abraham; Sertsu, Addisu; Dereje, Jerman; Debele, Gebiso Roba; Dechasa, Deribe Bekele (Frontiers in Psychiatry, 2023)
Background: Suicide is one of the most common public health problems and the second leading cause of death among individuals 15-29 years of age. Suicidal ideation and attempt are one of the common psychiatric emergence in patients with cancer that needs early detection and management before patients end their lives. Therefore, the aim of the study was to assess the magnitude of suicidal ideation, attempts, and associated factors among people with cancer in Eastern Ethiopia.Methods: An institutional-based cross-sectional study design was conducted among 362 participants. A composite international diagnostic interview was used to evaluate suicidal ideation and attempt. Epi-Data version 4.6.2 was used for data entry, and SPSS version 20 was used for analysis. Logistic regression analysis was done to identify associated factors for both suicidal ideation and attempt. P-values less than 0.05 are considered statistically significant, and the strength of the association will be represented by an adjusted odds ratio with a 95% confidence interval.